Self-Assembly of Peptide Bioconjugates: Selected Recent Research Highlights - Hamley, Ian W; Castelletto, Valeria (Bioconjugate chemistry, 2017)
This Topical Review briefly discusses selected highlights of recent research on self-assembling peptide amphiphiles (PAs) and polymer–peptide conjugates. Subjects covered include new polymer chemistries used to prepare polymer–peptide conjugates, PA self-assembly landscapes and kinetics, developments in the application of bioactive PAs and the relationship between self-assembly and bioactivity, novel PA/biopolymer composites, functional π-stacking peptide conjugates, use of enzymes to tune self-assembly, and developments in high throughput methods and the design and application of sequenced peptides.